Effects of GLP-1 Receptor Agonists on Biological Behavior of Colorectal Cancer Cells by Regulating PI3K/AKT/mTOR Signaling Pathway - Tong, Guoxiang; Peng, Tianhao; Chen, Ya; Sha, Lijuan; Dai, Huikang; Xiang, Yidong; Zou, Zhiqi; He, Heli; Wang, Sha (Frontiers in Pharmacology, 2022)
Colorectal cancer (CRC) is the top ten malignant tumor in incidence rate and mortality. Due to the lack of a good CRC screening program, most of the CRC patients have been transferred at the time of treatment. The conventional treatment can not effectively improve the prognosis of CRC patients, and the target drugs can significantly prolong the overall survival of patients with advanced stage. However, the use of single drug may lead to acquired drug resistance and various serious complications. Therefore, combined targeted drug therapy is the main alternative treatment with poor effect of single targeted drug therapy, which has important research significance for the treatment of CRC. Therefore, this study intends to culture CRC cell lines in vitro at the cell level and intervene with GLP-1 receptor agonist liraglutide. The effects of liraglutide on PI3K / Akt / mTOR signal pathway and CRC cell proliferation, cycle, migration, invasion and apoptosis are explored by detecting cell proliferation, cycle, migration, invasion and apoptosis and the expression of related mRNA and protein. The results showed that liraglutide, a GLP-1 receptor agonist, could block CRC cell cycle, reduce cell proliferation, migration and invasion, and promote apoptosis by inhibiting PI3K / Akt / mTOR signal pathway.